1983
DOI: 10.4315/0362-028x-46.5.412
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Survival of Staphylococcus aureus in Egyptian Domiati Cheese

Abstract: Domiati cheese was prepared from unsalted raw milk and from raw milk with 5 or 10% added sodium chloride, Milks were inoculated with enterotoxigenic Staphylococcus aureus strain 100 (produces enterotoxin A) before addition of salt and rennet. Cheeses were stored in whey containing 15% sodium chloride; were held at 30°C and were examined periodically for S. aureus count, aerobic plate count, DNase and moisture and salt contents. Numbers of S. aureus increased rapidly during preparation of cheese. There was a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…Then, the population of S. aureus decreased to the initial level of contamination after 75 days at a rate depending on salt concentration, starter activity and storage time. Conversely, in Domiati cheese, the presence of a high salt concentration (10% of sodium chloride) was advantageous to the growth of S. aureus when competing with LAB (Ahmed et al 1983). In Camero cheese, Olarte et al (2000) reported that the growth of S. aureus was higher in batches without starter, but they did not detect any SE.…”
Section: Fresh Cheesesmentioning
confidence: 97%
“…Then, the population of S. aureus decreased to the initial level of contamination after 75 days at a rate depending on salt concentration, starter activity and storage time. Conversely, in Domiati cheese, the presence of a high salt concentration (10% of sodium chloride) was advantageous to the growth of S. aureus when competing with LAB (Ahmed et al 1983). In Camero cheese, Olarte et al (2000) reported that the growth of S. aureus was higher in batches without starter, but they did not detect any SE.…”
Section: Fresh Cheesesmentioning
confidence: 97%
“… 69 However, it has been reported that increasing the amount of salt in the milk used for the manufacture of domiati cheese enhanced the survival of S. aureus in the cheese; this effect was probably due to the inhibition of the LAB by the high salt content. 70 …”
Section: Microbiological Quality Of White‐brined Cheesesmentioning
confidence: 99%
“…However, challenge studies have revealed that S. aureus and E. coli O157:H7 can survive the processing conditions used for a variety of cheeses, including domiati cheese (Ahmed et al . ; Nunez et al . ; Maher et al .…”
Section: Introductionmentioning
confidence: 99%